2015
DOI: 10.1021/ef5024803
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Primary Fragmentation of a Lignite during Fluidized-Bed (FB) Devolatilization

Abstract: The paper presents a comparison between experimental and model results of primary fragmentation of a lignite coal in a fluidized bed (FB). In the experiments, the char particle size distribution and the general indicators of primary fragmentation (intensity and index) were determined. The same parameters were calculated using a mathematical model of the process, fed by data of the fuel (the amount of volatiles and fixed carbon), fluidized bed temperature, and inlet particle size distribution. The size distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The FI value depends mainly on the F d value. F d would always be less than 1 if the fuel is of nonswelling type and when the fuel is of a swelling nature, the F d will be ≥1 . Since FI is inversely proportional to F d , the FI value will be ≤1 for swelling types and ≥1 for nonswelling and shrinking types.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FI value depends mainly on the F d value. F d would always be less than 1 if the fuel is of nonswelling type and when the fuel is of a swelling nature, the F d will be ≥1 . Since FI is inversely proportional to F d , the FI value will be ≤1 for swelling types and ≥1 for nonswelling and shrinking types.…”
Section: Resultsmentioning
confidence: 99%
“…If the crack develops in the inner radial positions of the fuel structure (due to the high volatile content of the fuel), it results in the formation of a larger daughter particle . The fracture originating in the outer radial locations due to the thermal stresses leads to exfoliation of outer layers, resulting in generation of fine particles . Thus, it can be understood that if most of the resulting fragments lie in the smaller particle size range, it denotes that the thermal stresses are predominant in creating fragments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In his experiments and simulation, the fragmentation probability of lignite is significantly higher than that of sub-bituminous coal. Paprika (Paprika et al, 2015) and Scala (Scala, 2016) also found the lignite coal particles partially breaks at the beginning of devolatilization, giving a large number of fine fragments. However, detailed description of the fragmentation behavior will make the model much more complex.…”
Section: Fuel Particles Balance and Volatiles Axial Distributionmentioning
confidence: 93%
“…1.0 (ii) The primary fragmentation of large fuel particles are considered, and the PAPSD is modified based on the model proposed in Ref. [61] (iii) The attrition of fuel and char particles is neglected due to the short time of devolatilization or combustion process.…”
Section: Hydrodynamics and Materials Balance (1-d)mentioning
confidence: 99%